Rancang Bangun Pengukuran Kadar Oksigen dan Denyut Jantung Dalam Darah Dengan Sistem Monitoring Berbasis Intermet of Things - Nur Alifia, Nur (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
Hemoglobin is a protein molecule in the blood that functions to bind oxygen. One of the most important indicators of oxygen supply in the body is oxygen saturation (SpO2). Because oxygen saturation (SpO2) can indicate whether hemoglobin can bind oxygen or not. To monitor the patient's oxygen levels and heart rate in real time using a smartphone uses a GYMax30100 type Max30100 sensor using NodeMCU ESP8266 as a microcontroller then the results will be sent to the output in the form of a Liquid Crystal Display (LCD) screen on the front of the device and monitored using the Blynk application on a smartphone. The results of smartphone testing on SpO2 get an average result of 97.04% and BPM of 79.77Bpm while in a positive condition the average result is 96.50% for SpO2 and 93.37Bpm for BPM. After measuring with a comparison tool under normal conditions, the average error value of the measurement was obtained, which was 2.26% while the positive condition was 2.00%